Elective endoscopic variceal ligation is not a risk factor for bacterial infection in patients with liver cirrhosis. Issue 4 (April 2018) - Maimone, Sergio; Saffioti, Francesca; Filomia, Roberto; Caccamo, Gaia; Saitta, Carlo; Pallio, Socrate; Consolo, Pierluigi; Sabatini, Sara; Sitajolo, Krizia; Franzè, Maria Stella; Cacciola, Irene; Raimondo, Giovanni; et al.
Abstract: Background: Patients with cirrhosis are at high risk of bacterial infections. Invasive procedures are generally believed to increase this susceptibility. Aims: We investigated the incidence of bacterial infections in cirrhotic patients undergoing elective endoscopic variceal ligation (EVL). Methods: We enrolled 60 consecutive cirrhotic patients who underwent a total number of 112 elective EVL procedures. One to seven bands were applied at each session until variceal eradication. Markers of inflammation/infection and blood cultures were obtained before and 24 h after EVL. Results: Aetiology of liver disease was metabolic in 27 (45%), viral in 21 (35%), alcoholic in 12 (20%) patients. Child–Pugh class A/B/C distribution was 29/26/5, respectively, 23 (38%) patients had ascites and 15 (25%) had hepatocellular carcinoma. Blood cultures were negative in all samples before EVL, whereas 3/112 (2.7%) cultures tested positive after endoscopy. Streptococcus mitis and Staphylococcus epidermidis were isolated in 1 and 2 cases, respectively. None of these three patients developed any features of clinically relevant infection, suggesting that the positive cultures were an expression of a transient bacteraemia with no clinical sequelae. Conclusions: Bacterial infection is an uncommon occurrence after elective EVL in cirrhotic patients, and antibiotic prophylaxis is not necessary in this clinical setting.